2022
DOI: 10.3389/fpls.2022.946194
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of PLATZ Transcription Factors in Ginkgo biloba L. and Their Expression Characteristics During Seed Development

Abstract: Plant AT-rich protein and zinc-binding protein (PLATZ) is a class of plant-specific zinc-dependent DNA-binding protein that binds to A/T-rich DNA sequences. PLATZ plays an important role in seed development, water tolerance, and cell proliferation in early plant growth. In this study, 11 GbPLATZs were identified from the ginkgo genome with complete PLATZ-conserved domains, which represents a smaller number compared with angiosperms. Multi-species phylogenetic analysis showed that PLATZ genes were conserved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Exploring the motifs distribution is meaningful to understanding gene function and their evolutionary history ( Han et al., 2022 ). We further investigated the conserved motifs of PLATZ genes, and 8 distinct motifs were identified in apple by the MEME program, designated motifs 1-8 ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Exploring the motifs distribution is meaningful to understanding gene function and their evolutionary history ( Han et al., 2022 ). We further investigated the conserved motifs of PLATZ genes, and 8 distinct motifs were identified in apple by the MEME program, designated motifs 1-8 ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cultivated tomatoes, in contrast to most higher plants, have 24 members of the PLATZ family. This number is comparable to cabbage and higher than the numbers for Arabidopsis [ 17 ] and Ginkgo [ 26 ]. Compared to Wai’s [ 27 ] findings, which discovered 20 SlPLATZ genes, this is different.…”
Section: Discussionmentioning
confidence: 68%
“…The zinc finger transcription factor PLATZ is widely present in plants and plays an important role in regulating plant growth and development and responding to abiotic stress. The transgenic Arabidopsis thaliana with GhPLATZ1 may promote seed germination and seedling formation under salt stress by increasing the GA and ethylene content and reducing the ABA content ( Han et al., 2022 ). It was found that PhePLATZ23 and PLATZ27 are highly responsive to cold stress and play an extremely important role in regulating bamboo’s response to external environmental stimuli ( Zhang et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%